CONVERGENCE OF LAGRANGE-HERMITE INTERPOLATION - Bahadur, Swarnima; Shukla, Manisha (Italian Journal of Pure and Applied Mathematics, 2014)
In this paper, we consider explicit representations and convergence of Lagrange–Hermite Interpolation on two disjoint set of nodes, which are obtained by projecting vertically the zeros of (1− x2) Pn(α,β) (x) and (1− x2) Pn(α,β)‘ (x) respectively on the unit circle, where Pn(α,β) (x) stands for Jacobi polynomials.